Prediksi Produksi Kerajinan Rotan Menerapkan Metode Tsukamoto - Anisa Agustina Melani; Muhammad Fajrin Anshari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Rattan handicrafts are one of the most famous handicrafts in all corners of the country. Over time, rattan handicrafts have grown in terms of types and forms. One of the industries that produces rattan handicrafts is Rattan Furniture-Sampit, located in East Kotawaringin, Central Kalimantan. The purpose of this research and application of this method is to predict the amount of rattan production based on material information and based on customer orders, because usually when there is an order the industry only estimates the amount of rattan to be used as crafts and results in more than customer orders. The final result of this research is to find the amount of handicraft production that must be produced based on demand and supply of materials